2018
DOI: 10.1038/s41416-018-0112-z
|View full text |Cite
|
Sign up to set email alerts
|

RT Prepare: a radiation therapist-delivered intervention reduces psychological distress in women with breast cancer referred for radiotherapy

Abstract: The RT Prepare intervention was effective in reducing breast cancer patients' psychological distress and preparing patients for treatment. This intervention provides an opportunity for radiation therapists to extend their role into providing patients with information and support prior to treatment to reduce psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 52 publications
0
54
0
3
Order By: Relevance
“…Briefly, of 218 controls and 190 intervention participants recruited, the mean ages were 55.9 and 57.9, the proportions in a relationship were 68.3% and 65.3%, English was spoken at home by 94.5% and 95.8%, chemotherapy had been received or was being received by 49.1% and 53.7%, 58.3% and 54.7% were employed or studying, and other health conditions were reported by 51.6% and 54.7%, respectively …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Briefly, of 218 controls and 190 intervention participants recruited, the mean ages were 55.9 and 57.9, the proportions in a relationship were 68.3% and 65.3%, English was spoken at home by 94.5% and 95.8%, chemotherapy had been received or was being received by 49.1% and 53.7%, 58.3% and 54.7% were employed or studying, and other health conditions were reported by 51.6% and 54.7%, respectively …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the pilot study showed a trend towards lower anxiety and concerns about radiotherapy and higher knowledge . Results of our large multisite study demonstrated that compared with usual care, intervention participants reported lower psychological distress at treatment commencement ( P = .01); lower concerns about radiotherapy ( P < .01); higher knowledge ( P < .001); higher preparedness for procedural concerns ( P < .001); and higher preparedness for sensory‐psychological concerns at treatment planning ( P < .001) …”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations